Stability of concentrated emulsions measured by optical and rheological methods: Effect of processing conditions-I. Whey protein concentrate - Lizarraga, M.S. (2008)
The effect of processing conditions (Ultra Turrax (UT) and valve homogeniser (VH)) and protein concentration (0.37-2.93% w/w) on stability of 50% o/w emulsions prepared with commercial WPC were investigated by optical and rheological methods. The UT emulsions were slightly or not flocculated and presented Newtonian behaviour. The D43 constantly decreased with increasing protein concentration, the UT emulsions becoming more stable to the creaming process. The VH emulsions presented flocculation and an appreciably smaller particle size, which also decreased with WPC until reaching stability. These emulsions were Newtonian at the lowest concentration but presented shear thinning and hysteresis at the other concentrations. The low-shear viscosity increased with WPC, which suggested that the extent of flocculation was protein concentration dependent. The VH emulsions showed more stability to the creaming process and presented a delay phase which, surprisingly, increased with protein concentration. These results could be explained by a structure formation through a flocculation mechanism, as a consequence of a depletion mechanism and bridging flocculation.